2019
DOI: 10.1186/s13054-019-2506-6
|View full text |Cite
|
Sign up to set email alerts
|

Adipose tissue protects against sepsis-induced muscle weakness in mice: from lipolysis to ketones

Abstract: Background: ICU-acquired weakness is a debilitating consequence of prolonged critical illness that is associated with poor outcome. Recently, premorbid obesity has been shown to protect against such illness-induced muscle wasting and weakness. Here, we hypothesized that this protection was due to increased lipid and ketone availability. Methods: In a centrally catheterized, fluid-resuscitated, antibiotic-treated mouse model of prolonged sepsis, we compared markers of lipolysis and fatty acid oxidation in lean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
82
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 72 publications
(91 citation statements)
references
References 75 publications
7
82
0
2
Order By: Relevance
“…Plasma concentrations of 3-HB and insulin were determined on day 2 in PICU or on day 1 for patients with a shorter PICU stay. Boxes show median and IQR, whiskers 10th and 90th percentile the development of muscle weakness [17]. Alternatively, 3HB may act through enhanced autophagy-driven cellular housekeeping [10], a pathway that was previously shown to be activated by late-PN in critically ill adults [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma concentrations of 3-HB and insulin were determined on day 2 in PICU or on day 1 for patients with a shorter PICU stay. Boxes show median and IQR, whiskers 10th and 90th percentile the development of muscle weakness [17]. Alternatively, 3HB may act through enhanced autophagy-driven cellular housekeeping [10], a pathway that was previously shown to be activated by late-PN in critically ill adults [13].…”
Section: Discussionmentioning
confidence: 99%
“…Ketone bodies or ketogenic diets have shown to increase endurance in healthy athletes [15] and to induce beneficial effects in animal models of brain injury [16]. Moreover, in a mouse model of sepsis, a ketogenic PN formula and supplementation of PN with 3HB have shown to protect against the development of muscle weakness [17].…”
Section: Introductionmentioning
confidence: 99%
“…Although clinical data are currently still lacking, a series of studies in mice, performed in search of mechanisms underlying protection against ICU-acquired weakness by obesity, revealed that increasing the availability of ketone bodies, either through stimulation of endogenous ketogenesis or through infusion of exogenous ketones, protected against sepsis-induced muscle weakness [103]. This interesting finding still needs to be further explored in patients.…”
Section: Avoiding Early Parenteral Nutritionmentioning
confidence: 99%
“…Skeletal muscle and adipose tissue are two key metabolic tissues that exhibit major functional and histological changes in sepsis survivors. 6 Analogous to cachexia syndrome, muscle and fat wasting post-sepsis can result in many detrimental outcomes that directly impact long-term mortality and quality of life including decreased locomotive capacity, respiratory dysfunction, and altered systemic metabolism. 7,8 Fundamentally, tissue homeostasis involves balancing pro-growth anabolic processes with breakdown-associated catabolism.…”
Section: Introductionmentioning
confidence: 99%